2016
DOI: 10.1002/cctc.201600456
|View full text |Cite
|
Sign up to set email alerts
|

Base‐Free Palladium‐Catalyzed Borylation of Aryl Chlorides with Diborons

Abstract: The base‐free palladium‐catalyzed borylation of aryl chlorides with diborons was achieved. The base‐free conditions offered acceptable functional group compatibility. Based on experimental and computational studies, it was shown that smooth boryl transfer from the diborons to the arylpalladium chloride was promoted by strong interaction between the Lewis acidic boron and the chlorine atom on palladium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 95 publications
2
21
0
Order By: Relevance
“…The aryl chloride borylation is always challenging, and there were no methods available for this transformation until 2001. The first example was reported by Ishiyama et al using Pd as a catalyst and subsequently scope was expanded by others using mainly Pd and few Ni catalyst systems. In 2014, Bedford et al reported iron catalyzed borylation of alkyl, allyl and aryl halides, but only chlorobenzene could be borylated in a poor yield of 5% . Metal-free photoinduced C–X and dual C–H/C–X borylation of haloarenes were reported by Larionov et al, and pyridine-catalyzed radical borylation of aryl halides was reported by Jiao et al, but only two aryl chlorides have been described in each case.…”
Section: Introductionmentioning
confidence: 99%
“…The aryl chloride borylation is always challenging, and there were no methods available for this transformation until 2001. The first example was reported by Ishiyama et al using Pd as a catalyst and subsequently scope was expanded by others using mainly Pd and few Ni catalyst systems. In 2014, Bedford et al reported iron catalyzed borylation of alkyl, allyl and aryl halides, but only chlorobenzene could be borylated in a poor yield of 5% . Metal-free photoinduced C–X and dual C–H/C–X borylation of haloarenes were reported by Larionov et al, and pyridine-catalyzed radical borylation of aryl halides was reported by Jiao et al, but only two aryl chlorides have been described in each case.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10a,13 ] At first, the boronic ester‐functionalized IM unit is prepared by a facile synthesis (Figure S1a, Supporting Information). [ 14 ] This functionalization allows IM to participate in any Suzuki cross‐coupling reactions, thus being expandable to produce many different types of CPs. [ 15 ] It is confirmed that boronic ester functional groups are not affected during the imine reaction, evidenced by nuclear magnetic resonance (NMR) and mass spectroscopy (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The base was selected as a key parameter as its role in these reactions has not been comprehensively explored and is not mechanistically understood. Although base-free versions of the borylation have been reported, 6 a carboxylate salt seems crucial for the reactivity of this system. A systematic base screen was performed using 4bromobenzonitrile as model substrate (eq 1).…”
Section: ■ Introductionmentioning
confidence: 99%